WEBINAR DAN PENDAMPINGAN DARING PENULISAN ARTIKEL HASIL PENELITIAN PADA JURNAL NASIONAL TERAKREDITASI BAGI GURU BAHASA INDONESIA TINGKAT SMA KOTA BENGKULU - Dian Eka Chandra Wardhana; Rokhmat Basuki; Noermanzah Noermanzah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
The understanding of Indonesian high school level teachers in Bengkulu City on writing scientific articles on research results is still low. This is evidenced by the small number of Indonesian language teacher publications in accredited national journals and it has an impact on teachers having difficulty advancing in rank. For this reason, the aim of this community service is to provide understanding to Indonesian high school teachers in Bengkulu City in writing scientific articles and how to publish them in accredited national journals through webinars and mentoring activities. The community service method uses webinars and online mentoring through the Zoom Cloud Meeting. Participants totaled 37 Indonesian high school teachers in Bengkulu City. Community service techniques use lecture, discussion, and practice techniques. Data collection techniques using questionnaires, documentation, and observation. The results of the webinar indicate that the Indonesian language teacher is able to write articles quite well, starting from writing titles, abstracts, introductions, methods, research results, discussions, conclusions and suggestions, and bibliography. However, some teachers still have difficulty in pouring out the introductory section, especially mapping research positions based on relevant research results, difficulty in pouring out the discussion, especially finding the novelty of their research results, and difficulty finding references from online journals. Then, from the results of mentoring, Indonesian language teachers still have difficulty in submitting and the process of fixing articles in the OJS system. Keywords: webinars; accompaniment; scientific journal articles; accredited national journal